FEEDBACK TO STUDENTSâ WRITING AT PLANNING STAGE FOR BETTER FINAL DRAFTS - Monalisa, Mrs (Reflective, 2013)
Writing skill is reasonably complicated to acquire by most of English Foreign Language (EFL) learners. In contrast, to write effectively becomes significance for them due to their accomplishment in academic life for the most part may depend on it. A number of efforts have been made to develop studentsâ writing skill such as applying various writing approach. One of the approaches which considered sufficient to meet the learnersâ need for writing essay is interactional approach. The essential factors in interactional approach are written input and feedback from both teachers and peers at every stage of writing. This paper will, subsequently, discuss the application of this approach at the prewriting stage namely generating ideas, and making outline. Since the cyclical process of writing tends to take time, the input and feedback from the lecturer on the studentsâ final drafts are more often considered final by them. Therefore, I rarely accepted the revised version of studentsâ final draft. This experience has led me to only share the progress of essay content.Keywords : Interactional Approach, Prewriting Stage, Content Accuracy